The Anglo-Saxon Cemeteries at Caistor-by Norwich and Markshall, Norfolk - Myres, J.N.L (Reports of the Research Committee of the Society of Antiquaries of London, 1973)
This is an account of excavations of the Anglo-Saxon cemeteries at Caistor-by-Norwich and Markshall, Norfolk. Included are descriptions of funerary practices and grave goods, together with an account of the methodology used to during the excavations.